Strategi Komunikasi Kementerian Energi dan Sumber Daya Mineral dalam Penyetaraan Jabatan Administrasi ke Jabatan Fungsional - Ramadani, Thoriq; Sofyaningrum, Eviana D (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2020)
This research examined a communication strategy which was applied during the implementation of the delayering policy in the Ministry of Energy and Mineral Resources (EMR). Delayering policy is a re-organization strategy which reduces bureaucracy by converting several administrative positions (middle manager) into functional/professional-based positions. Qualitative approach was used in this research with case studies method. Primary data was collected through interview, while secondary data was used through literature review. The research result identified a specific communication strategy that was applied during delayering policy implementation. Appointed communicators in this case were the First Echelon Managers who had previously got a direct message from the Minister of EMR, Second Echelon Managers, Third Echelon Managers, Fourth Echelon Managers, and Staffs within the Ministry of EMR. The target was set for all the Third Echelon Managers and Fourth Echelon Managers in the Ministry of EMR. Formulation of messages based on information from the Ministry of Administrative Reform and Bureaucratic Reform that no employee would be disadvantaged. Selection of media was by information dissemination during the meeting at every unit level and also through the WhatsApp Groups messages. Moreover, the dissemination of messages was carried out through a briefing by the Secretary General of the Ministry of EMR, discussions, and WhatsApp Groups. The expected effects were that the middle manager could comprehend and comply with the delayering policy. The research recommended that the Ministry of EMR needed to issue written guidance, such as a pocket book, that explained the delayering policy and its impact in order to suppress any potential resistance.